Fulfilling the criteria for CLP classification: the implications for substances under the EU chemicals legislation - Kättström, Diana; Beronius, Anna; Boije af Gennäs, Urban; Rudén, Christina; Ågerstrand, Marlene (Frontiers in Toxicology, 2024)
The CLP mandates manufacturers and importers to classify substances and mixtures according to hazard criteria, with notifications submitted to the European Chemicals Agency (ECHA). Substances meeting hazard criteria must be appropriately labelled and packaged to communicate hazards effectively. The CLP establishes hazard classification criteria but does not independently prohibit or restrict the use of hazardous chemicals. Instead, it serves as a basis for regulatory obligations in other specific regulations. This study investigates the regulatory implications of meeting hazard criteria under the CLP across EU regulations and directives listed in EU Chemicals Legislation Finder (EUCLEF). The results show that fulfilling criteria for human health hazard classes trigger regulatory obligations in the highest number of regulations/directives, with carcinogenicity, mutagenicity, and reproductive toxicity (CMR) leading to obligations in 19 of 20 pieces of legislation linked to the CLP. Conversely, physical, environmental, and ozone layer hazards are associated with fewer regulations and directives, and lead to fewer prohibitions. The study underscores the pivotal role of the CLP in EU chemical legislation and the need for coherence and consistency across regulations. While regulatory obligations are primarily aimed at substances meeting hazard criteria, the variability in self-classification notifications and limitations in harmonized classification processes were observed. Moreover, the complexity of the regulatory structure poses challenges for stakeholders and policymakers, including inconsistencies, compliance difficulties, and the need for frequent revisions. Addressing these challenges is critical for enhancing regulatory effectiveness and ensuring a more coherent and harmonized approach to chemical management in the EU.